2021
DOI: 10.5130/cjlg.vi25.7701
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the performance of South African municipal officials: stakeholders’ perspectives

Abstract: Since the inception of the democratically elected post-apartheid government, South Africa has experienced growing numbers of protests about inadequate provision of basic municipal services. Recent studies have revealed that the poor performance of municipal officials contributes towards poor municipal service delivery. This article is based on a study which used qualitative key stakeholder interviews to analyse the performance of South African municipal officials, specifically in the delivery of services. It f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Upon the official downfall of apartheid in 1994, a new democratic government was instated yet the social inequalities remain to this day. In 2010, approximately 66% of municipalities across the country faced a service delivery crisis, while Masiya et al (2019) found that 44% of individuals were dissatisfied with service delivery nationally 2,33 . This has been blamed on skills shortages, lack of accountability, corruption and dubious decision-making at local government level.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the official downfall of apartheid in 1994, a new democratic government was instated yet the social inequalities remain to this day. In 2010, approximately 66% of municipalities across the country faced a service delivery crisis, while Masiya et al (2019) found that 44% of individuals were dissatisfied with service delivery nationally 2,33 . This has been blamed on skills shortages, lack of accountability, corruption and dubious decision-making at local government level.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand is a group of scholars such as Cloete (2009) as well as Kariuki and Reddy (2017) who attribute poor performance in South African municipalities to inadequate use of evidence for decision-making owing to a fragmented approach to performance management. On the other hand, another group of scholars identifies political interference as the main reason for poor performance (Ndevu, 2022;Maqoko, 2015;Masiya, Davids & Manga, 2021). In corroborating this view, Kgatle (2017) attributes poor performance in Tshwane Metropolitan Municipality to interference of the ANC in the administration of the Municipality.…”
Section: The Analysis Of Poor Performance In South African Municipali...mentioning
confidence: 97%
“…Regarding education and upskilling, it is impossible for a single governmental body to effectively cater to all its citizens' needs (Masiya, Davids & Mangai 2019). Local government, including rural municipalities, and rural municipalities cannot operate optimally without provincial and national governments.…”
Section: Education/skillsmentioning
confidence: 99%